2002
DOI: 10.1159/000063645
|View full text |Cite
|
Sign up to set email alerts
|

Dropout from Brief Psychotherapy in Anorexia nervosa

Abstract: Background: Dropout from psychotherapy is an important issue that has received little systematic attention. This study investigated the phenomenon of dropout from brief psychotherapy for anorexia nervosa (AN). Methods: 99 outpatients suffering from AN of the restrictor type (n = 53) or binge/purging type (n = 46) were evaluated. Their clinical and personal characteristics were recorded, and body mass index was calculated for participants. They were administered the Eating Disorder Inventory-II (EDI-II), the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
53
1
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 41 publications
(58 reference statements)
9
53
1
8
Order By: Relevance
“…Behaviour and the human mind, however, cannot be adequately understood without an appreciation of the pivotal role played by anger. Studies have examined the relation of anger with hypertension and cardiac diseases [1][2][3][4][5][6][7][8][9][10][11][12][13][14], eating disorders [15][16][17][18][19][20][21][22][23][24][25], and personality disorders [26, pp 20-21; 27, pp 267-268], as well as many other psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Behaviour and the human mind, however, cannot be adequately understood without an appreciation of the pivotal role played by anger. Studies have examined the relation of anger with hypertension and cardiac diseases [1][2][3][4][5][6][7][8][9][10][11][12][13][14], eating disorders [15][16][17][18][19][20][21][22][23][24][25], and personality disorders [26, pp 20-21; 27, pp 267-268], as well as many other psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that treatment of non-suicidal self-injury in ED should focus on stabilizing affective states rather than on reducing affects like anger (Vansteelandt et al, 2013). Despite such findings, there is a lack of research on how to approach anger and aggression in the treatment of ED (Fassino, Daga, Piero, & Rovera, 2002;Krug et al, 2008;Miotto et al, 2003;Truglia et al, 2006).A specific evidence-based intervention protocol targeted at aggression is missing. In this respect, psychomotor therapy (PMT) -a body and movement oriented therapy frequently used in mental health care in the Netherlands and Belgium (Probst, Knapen, Poot, & Vancampfort, 2010) -may prove useful.…”
mentioning
confidence: 99%
“…It is suggested that treatment of non-suicidal self-injury in ED should focus on stabilizing affective states rather than on reducing affects like anger (Vansteelandt et al, 2013). Despite such findings, there is a lack of research on how to approach anger and aggression in the treatment of ED (Fassino, Daga, Piero, & Rovera, 2002;Krug et al, 2008;Miotto et al, 2003;Truglia et al, 2006).…”
mentioning
confidence: 99%
“…Na investigação do impacto de comorbidades psiquiátricas na decisão de continuar um tratamento para transtornos alimentares, são utilizados tanto diagnósticos estabelecidos quanto a presença de sintomas psiquiátricos. O diagnóstico do transtorno de personalidade borderline ou a presença de sintomas borderline foi relacionada ao abandono do tratamento para transtornos alimentares em diversos estudos (Coker, et al, 1993;Waller, 1997;Fassino et al, 2002;Fassino et al, 2003;Surgenor et al, 2004;Woodside et al, 2004;Zeeck et al, 2005). Maiores níveis de sintomas depressivos foram encontrados como fator de risco para o abandono do tratamento tanto para a anorexia como para a bulimia nervosa (Coker et al, 1993;Steel et al, 2000;Woodside et al, 2004 ) ou fator protetor a conclusão do tratamento (Zeeck et al, 2005 …”
Section: Transtornos Alimentares E Abandono Do Tratamentounclassified
“…Grande parte das pesquisas que investigou esta relação, não encontrou diferenças significativas entre as médias de idade entre quem completou o tratamento ou decidiu interrompê-lo sem a concordância médica seja esse tratamento oferecido na modalidade ambulatorial (Waller, 1997;Steel et al, 2000;Fassino et al, 2002;Fassino et al, 2003;Grave; 2008) hospitalar (Zeeck et al, 2005;Surgenor et al, 2004;Masson et al, 2007), em hospital -dia (Franzen et al, 2004), ou para adolescentes (Lock et al, 2006;Hoste et al, 2007).…”
Section: Análise Multivariadaunclassified